Anti bribery management system (abms) impelementation in govenrment institution - mitigating bribery risk by integrating iso 31000 into iso 37001 - Dwi Sesantiningsih, Rika; J. Susilo, Leo (The Indonesian Journal of Business Administration, 2019)
Abstract.Nowadays people are becoming more aware of bribery risk that can disrupt organizational goal achievement. Bribe brings big impact for any organization, start from financial loss until reputational damage that will ruin organization reliability. Triggered by three element of triangle of fraud, a perpetrator could execute bribery activities even involving its family member.Â  Considering its role and responsibility within oil and gas upstream industry that may exposed to bribery risk, SKK Migas has been implementing anti bribery management system based on ISO 37001 since 2017. This system rely heavily on optimum bribery risk assessment as reference to determine action to address bribery risk. By integrating ISO 31000 into ISO 37001, organization could use risk assessment based on ISO 31000 as a powerfull tools to produce optimum bribery risk assessment to mitigate the bribery risk. SKK Migas has implemented risk management based on ISO 31000 earlier in 2015. Using an established system by integrating ISO 31000 into 37001 could support the implementation of anti-bribery management system to mitigate the bribery risk. Considered the importance of mitigating bribery risk, this integration should be monitored to ensure that it will always bring optimum value for implementation of anti bribery managemen system.Â Keywords: Bribery Risk, Business Process, Integration, Mitigation, Risk Assessment